Nonverbal Communication as a Means of Social Integration: The Development of Nonverbal Communication in Primary Schoolers with Intellectual Disabilities - Zashchirinskaia, Oksana V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study of nonverbal communication in primary schoolers with intellectual disabilities is an urgent topic for medical psychology. Background: The purpose of this paper is to study nonverbal communication as a means of social integration. Method: The methodological basis of this study is represented by various theoretic methods of scientific cognition. Methods of synthesis and analysis, system analysis of data and analysis of literary sources were used. In the context of the study, papers of foreign authors on the topic of nonverbal communication were considered. Results: The study of the nonverbal communication development in primary school-aged children will allow for more successful socialisation of children with mild mental retardation, which in turn partially compensates for the intellectual impairment, and will also reduce the risks of social isolation. Conclusion: This study is of practical value for psychologists and educators who work with children with a certain level of intellectual disability.